Prevalence and Correlates of Perceived Infertility in Ghana. Issue 3 (22nd September 2020) - Polis, Chelsea B.; Otupiri, Easmon; Hindin, Michelle; Chiu, Doris W.; Keogh, Sarah C.; Aidoo, Cara; Larsen‐Reindorf, Roderick; Bell, Suzanne O.
Abstract: Perceived infertility is an understudied phenomenon in low‐ and middle‐income countries, where biomedical infertility can have severe consequences, particularly for women. We conducted a nationally representative survey of Ghanaian women, estimated the prevalence of and reasons for perceived infertility, and assessed factors associated with higher levels of perceived infertility using a partial proportional odds model. Among 4, 070 women, 13 percent believed they were "very likely" to have difficulty getting pregnant when they wanted to, 21 percent believed this was "somewhat likely, " and 66 percent believed this was "not at all likely." Reasons for perceived infertility varied by whether the respondent was currently seeking pregnancy. In multivariable analysis, several factors were associated with higher levels of perceived infertility, while unexpectedly, women who reported ever using contraception were less likely to report perceived infertility. Acknowledging the need to address infertility globally and understanding the role of perceived infertility are important components in supporting people's ability to decide whether and when to have children.